2018
DOI: 10.1016/j.neuron.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Mutations in MYORG Cause Autosomal Recessive Primary Familial Brain Calcification

Abstract: Primary familial brain calcification (PFBC) is a genetically heterogeneous disorder characterized by bilateral calcifications in the basal ganglia and other brain regions. The genetic basis of this disorder remains unknown in a significant portion of familial cases. Here, we reported a recessive causal gene, MYORG, for PFBC. Compound heterozygous or homozygous mutations of MYORG co-segregated completely with PFBC in six families, with logarithm of odds (LOD) score of 4.91 at the zero recombination fraction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(163 citation statements)
references
References 29 publications
7
149
0
Order By: Relevance
“…Genomic DNA of the probands and all available family members was isolated from peripheral leukocytes using standard protocols. Sanger sequencing was performed on the coding exon (exon 2) of the MYORG gene (NM_020702) with PCR primers as previously described . Cosegregation analysis of the identified mutations was performed on all available family members.…”
Section: Methodssupporting
confidence: 61%
See 3 more Smart Citations
“…Genomic DNA of the probands and all available family members was isolated from peripheral leukocytes using standard protocols. Sanger sequencing was performed on the coding exon (exon 2) of the MYORG gene (NM_020702) with PCR primers as previously described . Cosegregation analysis of the identified mutations was performed on all available family members.…”
Section: Methodssupporting
confidence: 61%
“…To date, biallelic MYORG mutations have been reported in 17 patients (including our cohort). In the previous report, 6 patients with biallelic MYORG mutations exhibited similar symptoms, including slurred speech (6 of 6), ataxia (5 of 6), and cognitive decline (3 of 6), 2 patients presented with migraines, and the other 4 patients seemed asymptomatic . Additional clinical features, including parkinsonism, seizures, psychotic symptoms, dysphagia, urinary disturbance, and constipation, were first observed in our cohort, which further expanded the phenotypic spectrum of PFBC caused by biallelic MYORG mutations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, there have been few studies reported so far, and the relationship between XPR1 and PFBC still requires further confirmation (Anheim et al., ; Legati et al., ). Very recently, we have identified MYORG as the first autosomal recessive gene for PFBC (Yao et al., ). Subsequently another research group reported a homozygous MYORG mutation in a PFBC patient, further confirming that MYORG is involved in the genetic etiology of PFBC (Peng, Wang, Chen, & Jiang, ).…”
Section: Introductionmentioning
confidence: 99%